HIV-1 Env Does Not Enable the Development of Protective Broadly Neutralizing Antibodies in an Experimental Autoimmune Encephalomyelitis Mouse Model - Siracusano, Gabriel; Finardi, Annamaria; Pastori, Claudia; Martinelli, Vittorio; Furlan, Roberto; Lopalco, Lucia (Frontiers in Immunology, 2021)
Recent studies showed that immunological tolerance may restrict the development of Env-specific autoreactive broadly neutralizing antibodies. This evidence is consistent with the finding that Env immunization of a systemic lupus erythematosus (SLE) murine model produced antibodies that neutralize tier 2 HIV-1 strains. In this study, we address the possibility of eliciting neutralizing anti Env antibodies in other autoimmune diseases such as multiple sclerosis (MS). While, as reported for SLE, we showed for the first time that a small number of HIV-1 negative, relapsing remitting MS patients exhibited antibodies with neutralizing properties, our attempts at inducing those antibodies in a EAE mouse model of MS failed. The success in eliciting Env-specific neutralizing antibodies might be related to the specific characteristics of the autoimmune disease, or it might rely in improving the vaccination design. Studies using mouse models are useful to gain insight in how HIV-specific neutralizing antibody responses are regulated in order to develop a protective HIV-1 vaccine.